2016
DOI: 10.5330/1096-2409-20.1.44
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of School Counselor Self-Efficacy with English Language Learners

Abstract: This exploratory quantitative study described school counselors' self-efficacy with English language learners. Findings suggest that school counselors with exposure to and experiences with English language learners have higher levels of self-efficacy. Statistically significant and practical differences in self-efficacy were apparent by race, U.S. region, size of English language learner population, and counselor training. This article presents implications for training and practice and recommendations for futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…These findings are noteworthy given that the majority of practicing school counselors are White women (Bruce & Bridgeland, 2012). The findings support Johnson et al’s (2017) study that indicated that Black school counselors had higher self‐efficacy than their White peers. A plausible explanation regarding gender differences could be due to male counselors being more likely to work in high schools, thus influencing their self‐efficacy positively.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are noteworthy given that the majority of practicing school counselors are White women (Bruce & Bridgeland, 2012). The findings support Johnson et al’s (2017) study that indicated that Black school counselors had higher self‐efficacy than their White peers. A plausible explanation regarding gender differences could be due to male counselors being more likely to work in high schools, thus influencing their self‐efficacy positively.…”
Section: Discussionsupporting
confidence: 86%
“…Within the school counseling literature, Bodenhorn, Wolfe, and Airen (2010) found that increased self‐efficacy positively correlated with use of the American School Counselor Association’s (ASCA; 2012) National Model and perceptions related to achievement and equity. Other researchers found that higher levels of self‐efficacy enhanced school counselors’ abilities to manage legal and ethical issues (Mullen, Lambie, Griffith, & Sherrell, 2016) and improved their work with English language learners (Johnson, Ziomek‐Daigle, Haskins, & Paisley, 2017).…”
Section: Counselor Self‐efficacymentioning
confidence: 99%
“…These barriers for success stack up and create a difficult context for ELL students as they learn to navigate unfamiliar school environments and cultures. School counselors are uniquely positioned to impact ELL academic success either positively or negatively because they contribute to cultural and community support, help strengthen student self-efficacy, and mitigate systemic barriers through advocacy (Johnson et al, 2016). Partnerships between parents, school, and community have proved to be highly effectual and cost-effective (Gonzalez et al, 2013); when such resources are culturally and linguistically appropriate, rates of success increase significantly (Aceves, 2014).…”
Section: Additional Barriersmentioning
confidence: 99%
“…Other reasons for underrepresentation of gifted ELLs include teacher bias, test bias, and inequality of educational opportunity (Worrell, 2015). Most studies have focused exclusively on Latinx/Spanish-speaking ELL students’ academic achievement or advocacy through community integration (Betters-Bubon & Schultz, 2017; Clark et al, 2012; Cook et al, 2012; Gonzalez et al, 2013; Harris & Sullivan, 2017; Villalba et al, 2007), and very few have focused on the complex needs of the ELL population as a whole (Johnson et al, 2016; McCall-Perez, 2000; Shi & Watkinson, 2019). Only a few articles involve the voices of the counselors who are directly working with this population.…”
mentioning
confidence: 99%
“…Self-efficacy literature within the school counseling profession examines a plethora of topics including supporting English-language learners (ELLs; Johnson et al, 2016), group facilitation (Springer & Schimmel, 2016), and programmatic services delivery (Mullen et al, 2019); all of which are related to comprehensive school counseling. Johnson et al (2016) focused on school counselor self-efficacy in providing services to ELL students, and the results indicated that professional training was statistically significant to increased confidence. Springer and Schimmel (2016) examined strategies to increase school counselor trainees’ self-efficacy in facilitating groups; resulting recommendations included scaffolded supervision of activities and didactic experiences.…”
Section: School Counselor Role and Best Practicementioning
confidence: 99%